THE IMPRESCRITIBILITY THESIS OF ENVIRONMENTAL DAMAGE IN GENERAL REPERCUSSION OF THE SUPREME FEDERAL COURT AND THE POSSIBILITY OF APPLYING THE AGGRAVATED RISK THEORY ON DIFFUSE RIGHTS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This article comes to appreciate the position of the Supreme Court on the imprescriptibility of the repair of environmental damages arising from environmental infractions, the theme is approached with the appreciation of a more holistic view on the problem of objective civil liability and its application to the responsible person “ eternal ”for the damage. In this tuning fork, the conditions of nexus and cause, in environmental damage, are the focus of a paradigmatic reflection, capable of seeking an effective construction of an understanding of the origin of the judgment (STF) and a reflection on the reason for the eternalization of the accountability of environmental infractions and its consequences, not just more theoretical practices as well. When dealing with the subject through the interpretation of the jurisprudence, a theoretical approach is made about the forms of reparation and its various theories, such as the rich integral and the risk caused, to later present a new idealization of the judgment. The present article does not seek to exhaust all situations and complexities arising from the Supreme Court's understanding of imprescriptibility, but it serves more to warn about a possible expansion of the utopian vision of exacerbated environmental protectionism, capable of producing harmful effects to activities that use the environment, so important for humanity itself, with the protection of natural resources.